Consent to Treatment in the Post-montgomery ERA: Principles and Implications for the Dental Team. Issue 2 (June 2019) - Blum, Igor R.; Hooper, Stephen
This paper examines recent changes in relation to the legal and regulatory requirements around the consent process in the UK and how to protect patients' rights to make decisions about their treatment. In addition to the implications of the Montgomery case on UK law of consent, key governmental and professional body regulatory guidance on the subject of consent are taken into account and discussed to facilitate a robust and valid consent process in the dental care environment.